352 Computational methods for predicting drug combinations for targeting KRAS mutations relevant to non-small cell lung cancer. (April 2022) - Bruggemann, Liana; Falls, Zackary; Mangione, William; Mahajan, Supriya; Samudrala, Ram
Abstract : OBJECTIVES/GOALS: Our goal is to develop a cost-effective approach for precision medicine treatment by providing computational predictions for new uses of currently available FDA approved, and experimental drugs for NSCLC. METHODS/STUDY POPULATION: Cell Lines: A549 (ATCC- CCL-185) Human epithelial Lung Carcinoma cells, H1792 (ATCC-CRL-5895) Human Lung Carcinoma cells. In Vitro Cytotoxicity Assay: A VybrantÂ® MTT Cell Proliferation Assay was used. Colony Formation Assay: NCI-H1792, A549 cells were seeded at a density of 500 cells/ dish, then treated with ARS-1620, Osimertinib. The Computational Analysis of Novel Drug Opportunities (CANDO): Â Herein, we employed the bioanalytic docking (BANDOCK) protocol within CANDO to calculate the compound-protein interaction scores for a library of 13, 218 compounds from DrugBank against a library of 5, 317 protein structures from the Protein Data Bank, resulting in a proteomic interaction signature for each compound, and identified Osimertinib as the most likely EGFR/ErbB inhibitor to synergize with ARS-1620. RESULTS/ANTICIPATED RESULTS: ARS-1620 and Osimertinib in combination displays potent anti-tumor activity as evident by a decrease in cell viability with cytotoxicity assays, as well as reduced number of colonies in the colony formation assay for both A549 and H1792 cells. By using CANDO, and cross-referencing the obtained rankings with known experimental information, we have obtained drug predictions within the context of precision medicine. Our preliminary data indicates that EGFR inhibitor Osimertinib may be most structurally similar to KRAS G12C inhibitors overall, compared to other ErbB/ EGFR inhibitors. Validations with human cancer cell lines A549 and H1792 have confirmed that Osimertinib in combination with KRAS G12C inhibitor ARS-1620 may exhibit a synergistic effect in decreasing cellular proliferation and colony formation. DISCUSSION/SIGNIFICANCE: This suggests that this innovative drug combination therapy may help improve treatment outcomes for KRAS G12C(H1792) and KRASG12S(A549) mutant cancers. Cell migration and cell invasion studies in response to treatment with Osimertinib and ARS-1620 are currently ongoing.